Kehidupan Keuangan Keluarga Muslim - Rini Purnamasari; Ahmad Abbas (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
Economic needs sometimes become one of the sources of problems in household life, but they can be solved if the family is built by good financial management. This research aims to demonstrate practices of household accounting by studying the life of muslim family. The type of this research is qualitative using a case study approach. Informants of this research were household units of muslim family. Data analysis in this research used reductions, displays, and inferences. The result of this research discloses that the conceptual framework of household accounting Islamic is found in muslim families under the method of recording cash basis. The practice of household accounting can be built in accounting cycles starting from transaction documents, recorded into general journals, conducted the posting into ledgers, prepared adjusting journals, and financial statements including activity, and financial position statements. Informants of muslim family in this research recognize the expenditure of Zakat, Infaq, and Shadaqah (ZIS) Keywords: Accounting; Islamic; Family; Financial Statements; Household